1986
DOI: 10.1364/ol.11.000516
|View full text |Cite
|
Sign up to set email alerts
|

Dye laser pumped by Nd:YAG laser pulses frequency doubled in a glass optical fiber

Abstract: Efficient frequency doubling of a cw Q-switched and mode-locked Nd:YAG laser has been observed in commercial single-mode optical glass fibers. Pulses of duration ~55 psec and intensities as high as ~0.55 kW were produced at 0.53 microm. The maximum peak power-conversion efficiency measured was ~3%. The frequency-doubled light generated in the glass fibers was sufficient to pump a commercial Rh6G dye laser with ~19% efficiency at 570 nm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
174
1
2

Year Published

1993
1993
2010
2010

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 570 publications
(184 citation statements)
references
References 3 publications
7
174
1
2
Order By: Relevance
“…As shown elsewhere [22], the case of perfect phase-matching Ak=0, together with the assumption of a completely random spatial distribution for the molecular displacement vectors R e, leads to the simple result rIN= N2( Ak=O) (7) so that the response given by Eq. (5) entails a quadratic dependence on the number of scatterers.…”
Section: Background; Treatment Of Ideal Molecular Fluidsmentioning
confidence: 89%
See 1 more Smart Citation
“…As shown elsewhere [22], the case of perfect phase-matching Ak=0, together with the assumption of a completely random spatial distribution for the molecular displacement vectors R e, leads to the simple result rIN= N2( Ak=O) (7) so that the response given by Eq. (5) entails a quadratic dependence on the number of scatterers.…”
Section: Background; Treatment Of Ideal Molecular Fluidsmentioning
confidence: 89%
“…A higher-order process entailing the coupling of harmonic conversions can result in production of an even harmonic through a mechanism involving an even number of electric dipole interactions [ 6]. It has also been suggested that the explanation for the observation of weak second harmonic signals gradually evolving in glass fibres is the formation of a grating or spatially periodic electric field, effectively destroying the symmetry of the bulk [7][8][9][10][11]. Indeed in these cases it is hard to rationalise the evolution of a second harmonic in terms of anything other than a structural effect.…”
Section: Introductionmentioning
confidence: 99%
“…χ (1) is directly related to the refractive index, n. χ (2) , is of most significance to poling; it describes how the refractive index varies linearly with applied field. Substituting E = Eapp + El(ω), where El(ω) is the field of the propagating light wave and Eapp is the applied electric field, into Eq.…”
Section: Optical Nonlinearitiesmentioning
confidence: 99%
“…Poling is the process that induces a non-zero χ (2) . χ (2) gives rise to the Second Order Nonlinearity (SON) and the Linear ElectroOptic (LEO) coefficient.…”
Section: Optical Nonlinearitiesmentioning
confidence: 99%
“…However, glass has the inversion symmetry, and therefore, glass should not generate the second order optical nonlinearity, χ (2) . This has generally brought glass materials only to passive usages like optical glass fibers, while second-order optical nonlinearity is the property absolutely required to active applications such as electrooptic switching and wavelength conversion by second-harmonic generation (SHG).…”
Section: Introductionmentioning
confidence: 99%